The mediating effects of first call resolution on call centers’ performance - Abdullateef, Aliyu Olayemi; Mohd Mokhtar, Sany Sanuri; Yusoff, Rushami Zien (Palgrave Macmillan, 2011)
This article aims to examine and validate the prepositions of the mediating impacts of first call resolution (FCR) on caller satisfaction within the contact center industry.A survey of 168 call center managers was analyzed through structural equation modeling, constituting an overall 43.3 per cent response rate for this study.The results show that FCR positively mediates the relationship between knowledge management, technology-based CRM and caller satisfaction within the inbound customer contact centers.We have empirically assessed call centers/contact centers’ success through caller satisfaction (an observed variable through their 2009 customer survey in Malaysia).Consequently, this study cannot generalize its findings in all other countries.Our strong argument is that within the operational variables, FCR is statistically significant and positively mediates knowledge management applications. But very important to note is that the customer contact centers are first touch points to a company's goods or services, and that many other factors such as product quality, company policy, target markets, decision-making processes and so on are also determinants of caller satisfaction, but fall outside the operational control of contact center activities.This research has empirically established that a company's capability in effectively acquiring a valid understanding of its current and potential customers’ information through CRM technologies will positively impact its acquisitions, customization, management and retention of customers.It also avails both the academic and contact center management the benefits that are inherent in measuring the impact of knowledge management and technology-based CRM on inbound FCR and caller satisfaction.This study finally recommends alternative areas for future research.